2022
DOI: 10.3389/fnins.2022.857009
|View full text |Cite
|
Sign up to set email alerts
|

Computational Mechanisms of Osmoregulation: A Reinforcement Learning Model for Sodium Appetite

Abstract: Homeostatic control with oral nutrient intake is a vital complex system involving the orderly interactions between the external and internal senses, behavioral control, reward learning, and decision-making. Sodium appetite is a representative system and has been intensively investigated in animal models of homeostatic systems and oral nutrient intake. However, the system-level mechanisms for regulating sodium intake behavior and homeostatic control remain unclear. In the current study, we attempted to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In conclusion, we showed that a homeostatic reinforcement learning theory can account for behaviors motivated by sodium appetite. A recent study also put forth a similar argument [ 62 ]—focusing on a different dataset, they showed that HRRL agents can match two-bottle test behavior for sodium and water choices. Here, we critically extend these ideas to show that the HRRL framework can also quantitatively account for the taste- and state-dependent DA responses, arguing that such DA signaling may in fact be causal for the learning of such appetitive behaviors.…”
Section: Discussionmentioning
confidence: 73%
“…In conclusion, we showed that a homeostatic reinforcement learning theory can account for behaviors motivated by sodium appetite. A recent study also put forth a similar argument [ 62 ]—focusing on a different dataset, they showed that HRRL agents can match two-bottle test behavior for sodium and water choices. Here, we critically extend these ideas to show that the HRRL framework can also quantitatively account for the taste- and state-dependent DA responses, arguing that such DA signaling may in fact be causal for the learning of such appetitive behaviors.…”
Section: Discussionmentioning
confidence: 73%
“…Future extensions of the HRRL framework could explore how competing drives interact and influence reward computations when multiple nutrients are available (i.e., hunger vs. thirst, blood osmolality and the drive for water vs. sodium). So far we (Keramati & Gutkin 2014; Keramati & Gutkin 2011) and others (Uchida et al 2022) have considered situations where multiple nutrient sources are independent in their impact on the internal state of the agent and therefore the drive function. Interestingly, we did show that under some conditions multiple sources do interact in their impact on shaping behavior in order to satisfy multiple constraints during behavioral policy formation (ref to Juechems).…”
Section: Discussionmentioning
confidence: 99%
“…HRL implements how organisms make decisions to keep their physiological state stable, i.e., the control of behavior by homeostasis, and has potential applications in explaining various behavioral phenomena in organisms (Juechems and Summerfield, 2019; Keramati and Gutkin, 2014; Uchida et al, 2022). This model defines reward as the proximity to a desired value for the internal state (i.e., setpoint).…”
Section: Introductionmentioning
confidence: 99%
“…A primordial source that drives animals to engage in specific behavior is physiological requirements, such as hunger and thirst. The idea of maintaining a steady physiological state, or homeostasis, has been applied to associative learning, habituation and sensitization, social behavior, and various behavioral phenomena (Eisenstein and Eisenstein, 2006; Juechems and Summerfield, 2019; Keramati and Gutkin, 2014; Lee et al, 2021; Uchida et al, 2022), suggesting that it has a potential to be applicable to human thoughts.…”
Section: Introductionmentioning
confidence: 99%